A comparative study of above- and below-ground parameters of healthy and declining young Norway spruce trees in a mountain area affected by air pollution. Issue 6 (18th August 2017) - Albrechtová, Petra; Mauer, Oldřich; Gebauer, Roman; Hurt, Václav; Kacálek, Dušan
ABSTRACT: The aim of this study was to characterize possible connections between above- and below-ground parameters and the decline of Norway spruce trees in the Jeseníky Mountains of the Czech Republic – an area affected both by long-term air pollution and subjected to liming. A part of this study was dedicated to soil analysis, which showed considerable changes in the soil environment and highlighted particularly high concentrations of magnesium and calcium, exceeding optimal limits by as much as 8 and 13 times, respectively. Our results suggest that the decline of evaluated trees is primarily connected to root system development, as we found no differences between evaluated above-ground parameters for either healthy or declining trees. Tree decline related directly to low numbers of skeletal roots, root origin and higher maximal angles between skeletal roots. Declining trees had on average five skeletal roots with maximal angles between them of 173 o, indicating poor mechanical stability. Regardless of tree vitality, 93% of all examined root systems were restricted to upper humus horizons with an average rooting depth of 10.2 cm. All evaluated trees showed severe root deformation into tangle, which suggests crucial influence of artificial planting on the architectural development of root systems.